Chilean Consensus for on Abobotulinumtoxin a (Dysport®): Indications, Techniques [Consenso Chileno Sobre Abobotulinumtoxina a (Dysport®): Indicaciones, Técnicas] - Chana-Cuevas, P (Sociedad de Neurologia Psiquiatria y Neurocirugia, 2013)
Botulinum neurotoxin is widely used to treat a variety of movement disorders, especially dystonia and spasticity. There botúlica different preparations of botulinum type A, that because biologics are difficult to compare. AbobotulinumtoxinA (Dysport ®) has recently been introduced in Chile for treating dystonia and spasticity. The aim of this paper is to provide a review by experts on the existing evidence and propose a practical guide to the use of the drug. Methods and Results: A group of Chilean experts met on 6 and 7 July 2012 to review AbobotulinumtoxinA doses along with injection protocols for dystonia, spasticity and other movement disorders. We worked in two groups, one composed of neurologists who reviewed the on dystonias and other by physiatrists who reviewed the indications for spasticity. Conclusions: Finally, there is a proposal in terms of dose, injection points and recommendations for dystonia and spasticity.